VD_FINDINFO Jug / 2011 / 239 vom 25. Oktober 2011 - VD Tribunal cantonal (2011)
PRÉVOYANCE PROFESSIONNELLE, RESTITUTIONEN GÉNÉRAL, PRESCRIPTION, PRINCIPE DE LA BONNE FOI | 83 LOJV, 25 al. 1 LPGA, 35a LPP, 49 al. 2 LPP, 73 al. 1 LPP, 73 al. 2 LPP, 73 al. 3 LPP, 5 al. 1 OPGA, 5 al. 4 OPGA, 93 al. 1 let. c LPA-VD